Non-enzymatic hydrolysis of fluorescein diacetate (FDA) in a Mediterranean oak (Quercus ilex L.) litter - Alarcón-Gutiérrez, E.; Floch, C.; Ruaudel, F.; Criquet, S. (European Journal of Soil Science, 2008)
We show the presence of interfering substances when the total microbial activity in litter samples is measured with fluorescein diacetate (FDA), and we propose some methodological modifications to avoid such interference. Three distinct litter layers (the OhLn, the OhLv and the OhLf) of evergreen oak (Quercus ilex L.) were characterized by 13C CPMAS NMR and the spectra show that the recalcitrant aromatic and phenolic compounds increase with the degree of degradation of litter. A wide range of sources of interference in the hydrolysis of FDA was found. To understand the origin of this interference, sterilized litter materials (i.e. γ-irradiated or autoclaved) and a wide range of organic substances (i.e. amino acids, glucose, sorbitol and organic humic acids) were investigated. Insignificant differences on the FDA hydrolysis activity (FDA activity) were found in the γ-irradiated and non-irradiated OhLn litter, indicating that γ-irradiation does not destroy enzymes. Conversely, after heat-sterilization of litter, samples showed FDA activity corresponding to 60, 34.8 and 30.8% (in the OhLn, the OhLv and the OhLf layers, respectively) of that of control litters. This indicates the presence of non-enzymatic interfering substances in the FDA assays. As the humification and litter depth increased, hydrolysis of FDA due to interferences decreased, indicating degradation and/or chelation of interfering substances. We hypothesize that lysine, arginine, histidine and cysteine are mainly responsible for the hydrolysis of FDA. We suggest that the use of phosphate buffer (50 mm, pH 7.0) with incubation < 30 minutes, in combination with a temperature between 30 and 40°C, produces insignificant interference in the determination of the final FDA activity in litter samples.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CPMAS 13C NMR spectroscopy (voyant); hydrolysis; litter; Soil